A Simple and Rapid Cryopreservation Technique for Ciliates: A Long‐Term Storage Procedure Used for Marine Scuticociliates. (12th April 2019) - Liu, Yongqiang; Nan, Bei; Duan, Lili; Cheng, Ting; Bourland, William A.; Liu, Mingjian; Zhao, Yan
Abstract: Pseudocohnilembus persalinus is a free‐living marine scuticociliate that, as a new model organism, has been used in a wide variety of studies. However, long‐term laboratory maintenance for this species is mainly achieved by subculture that requires rigorous culture environments and, too often, cultures of the organism die out for a variety of reasons. Successful transport of viable cultures also poses problems for researchers. This study describes a simple and rapid protocol for long‐term cryopreservation of P. persalinus . The effects of physiological states of individuals before freezing, the type and concentration of cryoprotectant, and optimal temperatures for freezing and thawing were assessed. A cryopreservation protocol, using a mixture of 30% glycerol and 70% concentrated P. persalinus cell culture, incorporating rate‐controlled freezing at −80 °C before liquid nitrogen storage, maintained a high recovery efficiency after 8 wk of storage. These results suggest that broader application of this protocol to build a cryopreserved marine protozoa culture bank for biological studies may be possible.